Low‐grade squamous intraepithelial lesions among women with HIV1. Issue 1 (24th April 2018) - Manamela, Portia K.; Kgomo, Koena A.; van Gelderen, Cyril J.; Lekha, Anushka R.; Michelow, Pamela; van den Berg, Eunice J.; Adam, Yasmin
Abstract: Objectives: To assess whether women with HIV who had low‐grade squamous intraepithelial lesions (LSIL) on cytology had cervical disease. Methods: The present retrospective cross‐sectional study included data from women with LSIL who attended a tertiary hospital in South Africa between April 1, 2003, and December 31, 2013. Patient information was extracted from a colposcopy database. Results: The study included 652 patients. The median age was 36 years (interquartile range [IQR] 31–42 years; range 18–66 years) and the median parity was three (IQR 2–5; range 0–10). In all, 266 (40.8%) women had a histology result of HPV or cervical intraepithelial neoplasia 1 (CIN1); 386 (59.2%) had a histology result of CIN2 or higher. The median cluster of differentiation 4 (CD4) count was 275.00 cells/mm 3 (IQR 173.50–434.00 cells/mm 3 ; range 2–1211 cells/mm 3 ). A total of 312 (47.9%) women were using antiretroviral therapy. Use of antiretroviral therapy (unadjusted odds ratio 0.57; P =0.001) and a CD4 count of at least 200 cells/mm 3 (unadjusted odds ratio 0.81; P =0.002) were associated with a histology result of HPV or CIN1. Conclusion: Most of the women with a cytology report of LSIL had CIN2 or higher, suggesting that the practice of referral for colposcopy should continue. Abstract : Most women with low‐grade squamous intraepithelial lesions on cytologic examination had cervical intraepithelial neoplasia 2, which suggested that referral for colposcopy should continue.